Pharmacogenetics of smoking cessation in general practice: results from the patch II and patch in practice trials. - David, S; Johnstone, E; Churchman, M; Aveyard, P; Murphy, M; Munafò, MR (2011)
INTRODUCTION: Cigarette smoking remains the leading cause of preventable death worldwide. However, the efficacy of available first-line therapies remains low, particularly in primary care practice where most smokers seek and receive treatment. These observations reinforce the notion that 'one size fits all' smoking cessation therapies may not be optimal. Therefore, a translational research effort was launched by the Imperial Cancer Research Fund (later Cancer Research UK) General Practice Research Group, who led a decade-long research enterprise that examined the influence of pharmacological hypothesis-driven research into genetic influences on drug response for smoking cessation with transdermal nicotine replacement therapy in general practice. METHODS: New and previously published smoking cessation genetic association results of 30 candidate gene polymorphisms genotyped for participants in two transdermal nicotine replacement clinical trials based in UK general practices, which employed an intention to analyze approach. RESULTS: By this high bar, one of the polymorphisms (COMT rs4680) was robust to correction for multiple comparisons. Moreover, future research directions are outlined; and lessons learned as well as best-practice models for designing, analyzing, and translating results into clinical practice are proposed. CONCLUSIONS: The results and lessons learned from this general practice-based pharmacogenetic research programme provide transportable insights at the transition to the second generation of pharmacogenetic and genomic investigations of smoking cessation and its translation to primary care.